MECCA MEAN TIME PROBLEMATIC AS A WORLD TIME REFERENCE - Raizza Kinka Intifada; Nuril Fathoni Hamas (Al-Hilal: Journal of Islamic Astronomy, 2021)
Desire of Muslims to replace the present standard of time, namely Greenwich Mean Time, to Mecca Mean Time is the manifestation of a new spirit in the Islamic world in particular. Mecca Mean Time makes al-Abraj tower (Mecca Royal Clock) the zero degree point or standard for the commencement of global time. The goal of this study is to find out what are the challenges that occur when Mecca Mean Time is used as a reference for global time. This research is a sort of qualitative research involving library research studies by describing descriptively. After the data is obtained, the author will categorize, analyze and present it in the form of a brief and systematic document. In this study, it was revealed that there was a debate of variations in views amongst different specialists when MMT was utilized as a reference for global time. Bambang Eko Budhiyono is striving very hard to achieve MMT as a world time reference on the basis of interpretation of the Qur'an verse 1 al-Hujurat. Meanwhile, Thomas Djamaluddin has a different perspective since physically and geographically there are no qualities that assist it to make it a time reference or as a main meridian (Prime Meridian) except religious spirit.